Lights in the shadows: Florence Nightingale and others who made their mark - Stanley, David (eContent Management, 2007)
Florence Nightingale, the 'lady with the lamp' became the image of 'heroic womanhood' (Bostridge 2004) when she returned from the Crimean War an iconic figure and ever since she has remained fated to wear the mantel of nursings' leading light. But she wasn't the only woman who made their mark or who undertook to risk their lives caring for the sick and injured, wounded and dying in the Crimea. Sadly, Nightingale's iconic status has also succeeded in overshadowing the existence and the achievements of the many others who nursed during the Crimean war. These women, nuns, ordinary nurses, lady volunteers and others, working in Nightingale's shadow, contributed much to the comforts of the wounded and dying and this article seeks to illuminate their presence and contribution. It also highlights other aspects of Nightingale's work in doing so, allows us to look into the shadows and shed more light on the others who were also there.